Evaluation and Management of Blepharoptosis - Pelton, Ron W. (Facial Plastic Surgery, 2022)
Drooping of the upper eyelid margin, aka blepharoptosis or “ptosis,” is common. Whether the ptosis is severe or mild, congenital or acquired, aponeurotic or neuropathic or myopathic, proper management always begins with a detailed history and evaluation of the patient. The information gathered will direct the surgeon in choosing the technique most likely to give the best result. This article will briefly review common causes of ptosis, the evaluation of the ptosis patient as well as the two most common types of surgical intervention.
Keywords: blepharoptosis; ptosis; levator resection; levator advancement; Müller's Muscle-Conjunctival Resection (MMCR)